2008
DOI: 10.1111/j.1600-0609.2008.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell transplant for POEMS syndrome is associated with high rates of engraftment syndrome

Abstract: Polyneuropathy, organomegaly, endocrinopathy, M protein and skin changes (POEMS) syndrome is a devastating syndrome, characterized by peripheral neuropathy, organomegaly, endocrinopathy, monoclonal plasma cells, skin changes, papilledema, volume overload, sclerotic bone lesions, thrombocytosis and high vascular endothelial growth factor (VEGF). High‐dose chemotherapy with autologous peripheral blood stem cell transplantation (ASCT) ultimately yields excellent clinical responses, but there can be considerable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 35 publications
6
116
1
Order By: Relevance
“…The incidence of ES after autotransplants in adults is 9-70% and correlates with the disease being treated. 2,3,[19][20][21][22][23][24] Pretransplant therapies also likely confound the incidence and presentation of ES. The highest incidences of ES are reported after autotransplants for breast cancer, 7,23 lymphomas other than Hodgkin lymphoma, 2 POEMS 24 and multiple sclerosis.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…The incidence of ES after autotransplants in adults is 9-70% and correlates with the disease being treated. 2,3,[19][20][21][22][23][24] Pretransplant therapies also likely confound the incidence and presentation of ES. The highest incidences of ES are reported after autotransplants for breast cancer, 7,23 lymphomas other than Hodgkin lymphoma, 2 POEMS 24 and multiple sclerosis.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…Six other cases of use with or after other alkylator based therapy yielded one death and 4 patients with improvement [22][23][24][25][26][27]176] High-dose chemotherapy with peripheral blood stem cell transplant can also be quite effective, but selection basis may confound these reports. Case series suggest 100% of patients achieve at least some neurologic improvement [18,54,87,140,[149][150][151][152][153][154][155][156][181][182][183][184][185]. Doses of melphalan ranging from 140 to 200 mg m 22 have been used, with the lower doses used for sicker patients.…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Imentioning
confidence: 99%
“…Symptomatic progressions were rare, whereas radiographic and VEGF progressions were most common. Treatmentrelated morbidity and mortality can be minimized by recognizing and treating an engraftment-type syndrome characterized by fevers, rash, diarrhea, weight gain, and respiratory symptoms and signs that occur anytime between days 7 and 15 post-stem cell infusion [154]. A starting dose of prednisone ranging between 20 and 1,500 mg day 21 has been used.…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Imentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, melphalan-based therapy has made significant progress in the treatment of POEMS syndrome, including chemotherapy of melphalan and dexamethasone, 3 and highdose melphalan followed by autologous PBSC transplantation. [4][5][6] Several studies have reported that autologous transplantation could achieve excellent clinical responses in patients with POEMS syndrome. However, this therapy was associated with high mortality of about 8%.…”
Section: Introductionmentioning
confidence: 99%